Pengaruh Promosi dan Lokasi terhadap Keputusan Pembelian pada Cafe Tabik di Bukittinggi - Nurfitriyenni, Nurfitriyenni (Jurusan PIPS FKIP UMMY Solok, 2018)
This study aims to determine whether promotions and locations influence the purchasing decisions at Tabik Café and analyze the most dominant factors in influencing the purchasing decisions of Tabik Café in Bukittinggi. Samples taken were 100 respondents. Sampling in this study uses probability sampling technique with simple random sampling method, which is that each individual has the same opportunity to be used as a research subject. From the results of Binary Logistic Regression analysis shows that there is a positive and significant influence between promotion and location on Purchase Decisions. The results of testing the regression model with the dependent variable purchasing decision obtained by the equation Y = -13.770 + 0.259 X1 + 0.556 X2. From the results of the analysis obtained the significance level of each Promotion variable (X1) is 0.039, location (X2) is 0.001. The results of the analysis show that each variable has a positive and significant influence on purchasing decisions at Tabik Café in Bukittinggi.